TECHNOLOGY OF FORMING MOVEMENT SKILLS IN SCHOOLCHILDREN - Kholova Shakhnoza Mardonovna; Nomozboyeva Rukhshona (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article covers effective technologies for forming movement skills in preschool children. The physical condition of children in movement, types of motor movements appropriate to the program age, methods of controlling movement activity through game analysis, movement changes and didactic analysis are studied and analyzed.